Complementary and Alternative Medicine use Among Cancer Patients - Sari, Ike Wuri Winahyu; Rukmi, Dwi Kartika (Universitas Respati Yogyakarta, 2020)
Although studies have shown that the use of complementary and alternative medicine (CAM) is common among cancer patients, there was limited data regarding CAM use among cancer patients in Indonesia. The aim of this study was to identify CAM use among cancer patients. This was a descriptive study with a cross-sectional approach conducted from July to August 2019 on 65 consenting cancer patients that selected purposively. Data were collected by sociodemographic questionnaires including a question about their CAM use. Data were analyzed using descriptive statistics. Overall, 29.2% reported that they had used or were using CAM. Herbal and vitamin supplement was the most commonly used in CAM (63.16%). Because there were still very few CAM users among cancer patients, it is important that health care professionals provide information about the CAM to the patients and aware of the extent to which cancer patients are using CAM.